RELATIONSHIP OF CONSUMPTION OF NEUROTROPIC SUPPLEMENTS WITH SYMPTOMS OF PERIPHERAL NEUROPATHY IN THE ELDERLY WHO SUFFER FROM TYPE 2 DIABETES - Wulandari, Ning Arti; Sari, Yeni Kartika; Desyana, Bety (STIKes Maharani Malang, 2020)
Type 2 diabetes is a disease characterized by insulin resistance and impaired insulin secretion, one of the risk factors associated with this disease is age. Elderly has decreased pancreatic function resulting in decreased insulin production which results in increased sugar levels. Uncontrolled sugar levels cause various complications, one of which is peripheral neuropathy. In the elderly program with chronic diseases, get neurotropic supplement therapy. Neurotropic supplements can protect nerves. The purpose of this study was to identify the relationship between consumption of neurotropic supplements with symptoms of peripheral neuropathy in the elderly who suffer from type 2 diabetes mellitus. Method: The design of this study was cross-sectional, carried out in the elderly program with chronic diseases in Garum and Banjarejo health centers. The sample of of this studies was 34 elderly who suffer from type 2 diabetes mellitus taken by accidental sampling with inclusion criteria elderly who do not suffer from diabetic foot ulcer. This study was taken by interviewing and examining peripheral neuropathy using the MNSI Instrument (Michigan Neuropathy Screening Instrument). The data obtained will be analyzed with the Spearman Rho test. The results of this study there was relationship between consumption of neurotropic supplements with symptoms of peripheral neuropathy in the elderly who suffer from type 2 diabetes mellitus with a value of P = 0.010. Discussion: the researcher recommends to the next researcher to conduct an experimental study about neurotropic supplementation in patients with type 2 diabetes mellitus. In order to get the right formulation in the use of neurotropic supplements to prevent peripheral neuropathy, given the increasing number of sufferers with diabetes mellitus